Yellow fever in Piura. Brief observations on its nature (conclusion) - Zapata, Carlos Emrique (1921)
The epidemic that has reigned and reigns in the Department of Piura, is imported from the city of Guayaquil. She came in from Tumbes, from early December 1918, brought by a traveling salesman. This city extended to petroleum centers Talara and Negritos in the months of March and April 1918. In April of that year, he died in Paita a patient who had previously been in Tumbes and Talara, presenting symptoms identical to cases seen in the above populations.